The Characterization of Natural and Artificial Calcium Carbonates by Adsorption and Immersion Techniques - Morel, Daniel; Stoeckli, Fritz; Kraehenbuehl, Francis; Misteli, Laurent; Munyazikwiye, Paulin (My University, 1985)
Nitrogen adsorption isotherms at 77K and enthalpies of immersion into water at 293K have been measured for a series of artificial and natural calcium carbonates. It appears that the external surface area and the micropore system can be fully characterized if a non-porous sample, present in the series, is used as an internal reference. Data are given for the reference isotherm. Owing to high specific interactions, immersion into water only provides information on the total surface area of the samples.